Proceedings of the International Conference on Communication and Signal Processing 2016 (ICCASP 2016) 2017
DOI: 10.2991/iccasp-16.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Manufacturing Parameters on Performance of Biodegradable Mg-Ca1.0 Implant

Abstract: Abstract:The paper reports the effects of machining parameters on performance of biodegradable magnesium calcium alloy implant in terms of surface roughness, microstructure, microhardness, chip morphology and degradation rate in face milling using CVD diamond like carbon coated carbide inserts. The result shows that the corrosion resistance of forged sample is higher than that of cast sample. It is also found that the surface roughness is the most significant factors affecting degradation rate. Degradation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Yan [ 25 ] et al compared experiments with magnesium alloy with cold air under pressure or dry cutting, and found that the former milling improved the surface quality and prevented magnesium alloy from burning easily during dry cutting. Desai [ 26 ] et al studied the influence of processing parameters on the properties of medical magnesium alloys. The results show that increasing cutting speed can improve the corrosion resistance and effectively alleviate pitting corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Yan [ 25 ] et al compared experiments with magnesium alloy with cold air under pressure or dry cutting, and found that the former milling improved the surface quality and prevented magnesium alloy from burning easily during dry cutting. Desai [ 26 ] et al studied the influence of processing parameters on the properties of medical magnesium alloys. The results show that increasing cutting speed can improve the corrosion resistance and effectively alleviate pitting corrosion.…”
Section: Introductionmentioning
confidence: 99%